Van Buchem disease. Issue 622 (August 1977) - Jacobs, P.
Abstract : Van Buchem disease is a hereditary sclerosing dysplasia of bone. Both dominant and autosomal recessive modes of transmission have been described. The dominant form tends to be a benign disorder and symptoms are usually confined to those associated with the enlargement of the jaw. The recessive forms tend to have a greater morbidity and symptoms arise from pressure on cranial nerves by hyperostotic bone at the base of the skull. Patients of the dominant families have often had a torus palatinus. No haematological changes are found. The alkaline phosphatase may be raised--even if the total level is not elevated, the bone fraction may be increased. The radiological appearances are regarded as characteristic. The jaw is enlarged and thickened to an extent not seen in other bone dysplasias such as osteopetrosis. The cortices of the diaphyses are thickened and the medullary cavities are encroached upon but not obliterated. Abnormal modelling of the bone ends is not found in van Buchem disease. In long bones the distribution is predominantly diaphyseal but the bone ends are also affected.